2020
DOI: 10.21082/jtidp.v7n3.2020.p127-136
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Nanoemulsi Minyak Serai Wangi Terhadap Phytophthora palmivora Butl. Patogen Busuk Buah Kakao

Abstract: <p><em>Black pod disease caused by </em>Phytophthora palmivora<em> is a significant disease on cocoa crops worldwide. Citronella and geraniol are two dominant substances of citronella oil that have fungicidal activity, which is potentially used to control black pod disease. However, those two substances are relatively unstable form volatile. To improve stability can be done using nanotechnology. The study aimed to analyze the effectiveness of citronella-oil-nanoemulsions formulas on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Then [24] tested citronella nanoemulsion to inhibit the growth of several pathogens such as Pestalotia longisetula, Fusarium oxysporum, Macrophomina phaseolina, and Alternaria raphani. Furthermore, [8] that the citronella oil nanoemulsion formula at a concentration of 0.5% can inhibit the growth of P. palmivora with an inhibitory power of 23.11%-77.78% compared to the control (in vitro). The activity of citronella oil nanoemulsion affects the growth rate of fungi, fresh and dry weight of fungi.…”
Section: Effect Of Eucalyptus Oil Nanoemulsion Formulation On the Gro...mentioning
confidence: 98%
See 1 more Smart Citation
“…Then [24] tested citronella nanoemulsion to inhibit the growth of several pathogens such as Pestalotia longisetula, Fusarium oxysporum, Macrophomina phaseolina, and Alternaria raphani. Furthermore, [8] that the citronella oil nanoemulsion formula at a concentration of 0.5% can inhibit the growth of P. palmivora with an inhibitory power of 23.11%-77.78% compared to the control (in vitro). The activity of citronella oil nanoemulsion affects the growth rate of fungi, fresh and dry weight of fungi.…”
Section: Effect Of Eucalyptus Oil Nanoemulsion Formulation On the Gro...mentioning
confidence: 98%
“…According to [7], the vegetable fungicide formula of clove and citronella oil enriched with salicylic acid and silicon at a concentration of 0.5% (5000 ppm) can reduce the intensity of cacao pod rot disease by 20.48%-65.62%. Furthermore [8], citronella oil nanoemulsion formula at a concentration of 0.5% (500 ppm) could inhibit the growth of P. palmivora with an inhibitory ability ranging between 23.11%-77.78% compared to the control (in vitro). The activity of citronella oil nanoemulsion affects the growth rate, dry and fresh weight of fungi.…”
Section: Introductionmentioning
confidence: 97%
“…Using citronella essential oil to control plant pathogenic fungi is proven to suppress fungal growth, but several weaknesses exist. Citronella essential oil has a volatile and unstable weakness, so its effectiveness decreases [9].…”
Section: Introductionmentioning
confidence: 99%
“…Endophytic bacteria are used as biological agents because they can control pathogens, increase plant growth, and induce plant resistance [13][14][15]. The use of endophytic bacteria to control nematodes in coffee plants is reported by [16], results showed that endophytic bacteria can suppress P. coffeae and increase plant growth. Furthermore, [2] reported that endophytic bacteria can suppress the number of gall and the nematode population of Meloidogyne spp.…”
Section: Introductionmentioning
confidence: 99%